Rhinolekos capetinga: a new cascudinho species (Loricariidae, Otothyrinae) from the rio Tocantins basin and comments on its ancestral dispersal route - Roxo, Fabio F. [UNESP]; Ochoa, Luz E. [UNESP]; Silva, Gabriel S. C. [UNESP]; Oliveira, Claudio [UNESP] (Pensoft Publ, 2015)
The present study deals with the description of a new species of Rhinolekos. It can be distinguished from its congeners by having 31 vertebrae, the anterior portion of the compound supraneural-first dorsal-fin proximal radial contacting the neural spine of the 9th vertebra, the absence of transverse dark bands in the pectoral, pelvic and anal-fin rays, 24-28 plates in the dorsal series, the lack of odontodes on the ventral tip of the snout, the absence of accessory teeth, a greater prenasal length, a smaller head length, and by a greater snout length. Rhinolekos capetinga is restricted to the headwaters of the rio Tocantins and it is the first species of this genus in the Amazon basin. Additionally, we present a brief discussion of a biogeographic scenario that may explain the dispersal of the new species from the rio Paranaiba to the rio Tocantins basin. We suggest that the ancestral lineage of R. capetinga reached the rio Tocantins from portions of the rio Paranaiba at the end of the Miocene, about 6.3 Mya (4.1-13.9 Mya 95% HPD), probably as a result of headwater capture processes among adjacent drainages.
Keywords: Biodiversity; Freshwater; Neotropical fish; South America; Taxonomy